2023
DOI: 10.3389/fcell.2023.1116805
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming in cancer: From diagnosis to treatment

Abstract: Disruption of the epigenetic program of gene expression is a hallmark of cancer that initiates and propagates tumorigenesis. Altered DNA methylation, histone modifications and ncRNAs expression are a feature of cancer cells. The dynamic epigenetic changes during oncogenic transformation are related to tumor heterogeneity, unlimited self-renewal and multi-lineage differentiation. This stem cell-like state or the aberrant reprogramming of cancer stem cells is the major challenge in treatment and drug resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 227 publications
(268 reference statements)
0
3
0
Order By: Relevance
“…Epigenetic reprogramming, which leads to changes in the cell landscape, is emerging as a promising preventive or therapeutic strategy for diseases. 78,79 The inhibition of epigenetic modifications by certain compounds could attenuate the chemical-induced neurotoxic effects. 80 The present study's major strength is that we evaluated the potential functional consequence associated with arsenic-related DMPs, and the clear association with clinical phenotypes underscores the necessity for further development of such biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic reprogramming, which leads to changes in the cell landscape, is emerging as a promising preventive or therapeutic strategy for diseases. 78,79 The inhibition of epigenetic modifications by certain compounds could attenuate the chemical-induced neurotoxic effects. 80 The present study's major strength is that we evaluated the potential functional consequence associated with arsenic-related DMPs, and the clear association with clinical phenotypes underscores the necessity for further development of such biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of normal epigenetic regulation of gene expression is a hallmark of cancer and contributes to human tumor development and progression. As epigenetic changes are reversible, they represent a potential target for cancer therapy [125].…”
Section: Epigenetic Modulationmentioning
confidence: 99%
“…DNA methylation by DNA methyltransferase enzymes (DNMT) typically represses gene transcription. Thus, DNA hypermethylation may reduce the expression of key tumor suppressor genes in human cancers, and tumor cells in cHL have been found to be characterized by a high number of hypermethylated genes [125,126]. DNMT inhibitors (DNMTi) such as azacitidine and decitabine could reverse this aberrant epigenetic regulation and have already been shown to be effective on myelodysplastic syndromes and acute myeloid leukemia [127,128].…”
Section: Dna Methyltransferase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that histone methylation plays a vital role in regulating ncRNA expression 48 . In esophageal cancer, EZH2, as a histone methyltransferase, promotes esophageal cancer cells' invasion and EMT process by upregulating miR-200c.…”
Section: Methylation To Ncrnasmentioning
confidence: 99%